Automorphisms of C* Moduli Spaces Associated to a Riemann Surface - Baraglia, D.; Biswas, I.; Schaposnik, L.P. (Symmetry, Integrability and Geometry: Methods and Applications, 2016)
We compute the automorphism groups of the Dolbeault, de Rham and Betti moduli spaces for the multiplicative group C∗ associated to a compact connected Riemann surface.